Gene expression differences in nitric oxide and reactive oxygen species regulation point to an altered innate immune response in chronic rhinosinusitis. Issue 3 (7th November 2012) - Jardeleza, Camille; Jones, Damien; Baker, Leonie; Miljkovic, Dijana; Boase, Samuel; Tan, Neil Cheng‐Wen; Vreugde, Sarah; Tan, Lor Wai; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background The complex interplay between host, environment, and microbe in the etiopathogenesis of chronic rhinosinusitis (CRS) remains unclear. This study focuses on the host‐microbe interaction, specifically the regulation of nitric oxide (NO) and reactive oxygen species (ROS) against the pathogenic organism Staphylococcus aureus (S. aureus). NO and ROS play crucial roles in innate immunity and in the first‐line defense against microbial invasion. Methods Sinonasal tissue samples were harvested from CRS and control patients during surgery. CRS patients were classified S. aureus biofilm‐positive (B+) or biofilm‐negative (B−) using fluorescence in situ hybridization and clinically as polyp‐positive (P+) or polyp‐negative (P−). Samples were assessed using an NO polymerase chain reaction (PCR) array containing 84 genes involved in NO and ROS regulation, and gene expression of all subgroups were compared to each other. Results Twenty‐three samples were analyzed with 31 genes significantly changed, the greatest seen in the B+P+ CRS patients. Four genes consistently displayed differential expression between the groups including the cytoprotective oxidation resistance 1 (OXR1) and peroxiredoxin 6 (PRDX6), neutrophil cytosolic factor 2 (NCF2), and the prion protein (PRNP) genes. Conclusion Alteration in gene expression points to impaired innate immune responses differing among CRS subgroups based on S. aureus biofilm and polyp status. The consistent alteration of 4 genes among distinct groups demonstrates that S. aureus biofilms and polyps are associated with specific changes in gene expression. Further studies are required to validate these findings in a wider cohort of patients and correlate this to protein expression and disease manifestation.